The Distinction of Agility Exercise Method and Flexibility Toward The Front Kick Legerity Development of Tapak Suci Pencak Athletes in Temanggung 2018 - Pradana, Toufan Wahyu; Nasuka, Nasuka; Rumini, Rumini (Journal of Physical Education and Sports, 2019)
Objective: (1) It is aimed to reveal and analyze the distinction between cone exercise method and reflective wall exercise method toward legerity of front kick development. (2) It is aimed to reveal and analyze the distinction between cone exercise and reflective wall exercise method for high flexibility and low flexibility athletes. (3) It is aimed to reveal and analyze the interaction between the cone exercise and reflective wall exercise method and flexibility toward front kick legerity development. The method of research is experimental research method with 2x2 factorial design.The analysis employed ANOVA (analysis of Variants) with significance (α) level on 0.05.Agility exercise roles as the research variable as cone and reflective wall roles as the free variableHigh flexibility and low flexibility role as the attribute variable, while front kick role as the bound varable.The population is 33 Temanggung Tapak Suci Pencak athletes (teenage).Sampling technique employed purposive sampling which results in 20 athletes.Research instrument are flexibility test as well as front kick legerity test.The result shows: (1) That reflective wall agility exercise is better than cone exercise method as Fvalue > Ftable or 22.231 > 3.59. (2) That athletes who poses high flexibility are better than those who poses low flexibility since it shows Fvalue > Ftable or 64.692 > 3.59. (3) That there is interaction between cone exercise and reflective wall exercise method to front kick agility since Fvalue >Ftable or  6.231 > 3.59.